Long-term outcomes of mandibular kinematics following class II malocclusion therapy with removable functional appliance therapy. Issue 6 (1st November 2016) - Linsen, Sabine S.; Wolf, Michael; Müßig, Dieter
Abstract : Objective: To evaluate mandibular kinematics in class I adults following class II therapy with removable functional appliances (RFAs) during the growth period in comparison with orthodontically untreated class I and II individuals. Methods: Condylar (CRoM) and incisal range of motion (InRoM), velocity during opening and closing, and the mandibular rotation angle were recorded using an ultrasound-based jaw-tracking system in 36 test patients (mean age = 28.03 ± 6.58 years). Results: Significant group effects were found for CRoM towards the posterior in the right joint ( p = 0.002) and InRoM towards the anterior ( p = 0.043). The post hoc Tukey test indicates a significantly longer CRoM (posterior) for the right condyle in class II ( p = 0.003) and RFA individuals ( p = 0.023). Discussion: The kinematic data imply greater dentoalveolar effects due to RFA therapy than adaptive remodeling of the temporomandibular joint. The class I relationship in the RFA group following treatment indicates stable long-term outcomes.